2020
DOI: 10.1103/physreva.102.033332
|View full text |Cite
|
Sign up to set email alerts
|

Stückelberg interferometry using spin-orbit-coupled cold atoms in an optical lattice

Abstract: Time evolution of spin-orbit-coupled cold atoms in an optical lattice is studied, with a two-band energy spectrum having two avoided crossings. A force is applied such that the atoms experience two consecutive Landau-Zener tunnelings while transversing the avoided crossings. Stückelberg interference arises from the phase accumulated during the adiabatic evolution between the two tunnelings. This phase is gauge field dependent and thus provides new opportunities to measure the synthetic gauge field, which is ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…(Zenesini et al, 2010), where the respective double-passage model was used for a description of the experiment. These systems can also be used for multipassage interferometry (Béguin et al, 2022;Liang et al, 2020;Plötz and Wimberger, 2011).…”
Section: E Microscopic Systemsmentioning
confidence: 99%
“…(Zenesini et al, 2010), where the respective double-passage model was used for a description of the experiment. These systems can also be used for multipassage interferometry (Béguin et al, 2022;Liang et al, 2020;Plötz and Wimberger, 2011).…”
Section: E Microscopic Systemsmentioning
confidence: 99%
“…This novel ground state phase of the interacting Bose-Hubbard flux ladder provides superior conditions for the generation of multiple equilibrium states and becomes an ideal platform for the study of nonequilibrium quantum dynamics. Stability and superfluidity, chiral Bloch-Zener dynamics, Stückelberg interference, critical slowing down of the collective modes, and dynamical supersolidlike phases are presented [54][55][56][57][58][59][60][61][62][63]. However, which nontrivial nonequilibrium quantum dynamics can be excited by applying an external perturbation to resonantly couple the two degenerate quantum states in Bose-Hubbard flux ladder has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the dynamic research of the magnetic ladder system, it is shown that there are also abundant nonlinear dynamic characteristics in this system, e.g. chiral Bloch-Zener dynamics, Stückelberg interference, critical slowing down of the collective modes, dynamics supersolidlike phases, and nonequilibrium quantum dynamics [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%